SAT0373 Evaluation of american college of rheumatology provisional composite response (CRISS) index in the fasscinate trial. (15th June 2017) - Khanna, D; Berrocal, V; Denton, C; Jaheris, A; Spotwood, H; Lin, C; Siegel, J; Furst, D
Abstract : Background: Treatment with tocilizumab (TCZ) in early systemic sclerosis (SSc; FaSScinate trial) resulted in consistent, but not statistically significant, improvements in skin sclerosis (mRSS) at wks 24 and 48 1 . The CRISS index has been proposed as a composite index for trials in SSc 2 . CRISS is a 2-step process that assigns a probability of improvement for each subject ranging from 0.0 [no improvement] to 1.0 [marked improvement]. Step 1 assesses clinically meaningful decline in cardio-pulmonary-renal involvement and assigns a probability of 0.0. For remaining subjects, 5 variables are used to calculate probability of improvement. These are: FVC%, mRSS, patient (PT GA) and physician globals (MD GA), and HAQ-DI. Objectives: To assess the performance of CRISS index in the FaSScinate trial. Methods: In FaSScinate, pts ≥18 y with active SSc were randomized 1:1 to TCZ or placebo (PLA) for 48 wks. Step 1 CRISS was captured using review of serious adverse event data. Non-parametric Wilcoxon test was used to assess significant differences between the CRISS scores in both arms. Analyses were carried out for subject who had complete data at baseline and 24 weeks and at baseline and 48 weeks. Results: 87 pts (43 TCZ, 44 PBO) were enrolled. Baseline characteristics were similar between arms. 4 subjects in the PBO group and none in TCZ met the pre-defined definition of worsening in Step 1 and were given a score of 0.0. For remaining subjects, we calculated probability score for each subject. Using CRISS as a continuous measure, the median score was statistically significant and favored TCZ compared to PBO at wks 24 and 48 (p=0.04 and 0.01; Table). Table also presents the individual components of Step 2 where only FVC% was statistically significant favoring TCZ at wk 48. Conclusions: In this post-hoc analysis, CRISS index was able to discriminate TCZ from PBO, supporting its validity in an independent cohort. References: Khanna D. Lancet. 2016. Khanna D. Arthritis Rheum. 2016. Disclosure of Interest: D. Khanna Grant/research support from: NIH/NIAMS and NIH/NIAID, BMS, Pfizer, Consultant for: Actelion, Bayer, BMS, Boehringer Ingelheim, Genentech/Roche, Sanofi-aventis, GSK, Corbus, Cytori, EMD Serono, V. Berrocal: None declared, C. Denton Consultant for: Actelion, Bayer, GSK, CSL Behring, Merck-Serono, Genentech-Roche, Inventiva, Sanofi-Aventis, Boehringer Ingelheim, A. Jaheris Shareholder of: Roche stock and options, Employee of: Genentech, H. Spotwood Employee of: Roche, C. Lin Employee of: Genentech, J. Siegel Employee of: Genentech, D. Furst Grant/research support from: Amgen, BMS, NIH, Novartis, Pfizer, Roche/Genentech, Consultant for: AbbVie, Amgen, BMS, Cytori, Novartis, Pfizer, Roche/Genentech, UCB